Exercise-induced modulation of myokine irisin in bone and cartilage tissue—Positive effects on osteoarthritis: A narrative review - Ning, Ke; Wang, Zhuo; Zhang, Xin-an (Frontiers in Aging Neuroscience, 2022)
Osteoarthritis is a chronic degenerative musculoskeletal disease characterized by pathological changes in joint structures along with the incidence of which increasing with age. Exercise is recommended for all clinical treatment guidelines of osteoarthritis, but the exact molecular mechanisms are still unknown. Irisin is a newly discovered myokine released mainly by skeletal muscle in recent years - a biologically active protein capable of being released into the bloodstream as an endocrine factor, the synthesis and secretion of that has been shown to be specifically induced by exercise-induced muscle contraction. Although the discovery of irisin is relatively recent, its role in affecting bone density and cartilage homeostasis has been reported. A series of studies on irisin have provided new insights into the mechanisms of exercise training in improving bone density, resisting cartilage degeneration and maintaining the overall environmental homeostasis of the joint. The studies have further contributed to the understanding of the role of exercise in the fight against osteoarthritis. This article provides a review of the research findings on the regulation of irisin in relation to bone and cartilage, with a view to informing and assisting the development of the field for osteoarthritis treatments.